Economic populism and institutional changes in wage-labor relations - Unal, Emre (Springer Heidelberg, 2021)
John R. Commons emphasized the legislative role of governments in wage-labor relations, which instituted collective bargaining for labor organizations. Hence, workers largely abandoned ideas of cooperative production and socialism. This represented an institutional change in the balance power between the working class and industries. The present work discusses the case of the Turkish economy. When wage-labor relations were institutionalized in the 1960s, a strong bond between the working class and the government was established. The institutionalization of the wage-labor relationship gave considerable power to the working class, which in turn influenced government's economic policies. This was the birth of economic populism. This institutionalization became a major obstacle to economic stability and caused a deep path dependency that resulted in chronic inflation and unstable exchange rates for decades.
Keywords: Economic populism; Input-output analysis; Institutional changes; Path dependency; Turkey